The willingness of future teachers for professional selfimprovement - Liudmyla Matsuk (Vasyl Stefanyk Precarpathian National University, 2017)
The main stages of future teachers' willingness for professional self-improvement are outlined in the article. It is proved that the organization of professional teacher's training on the principles of humanization and personalization, unity of common cultural, personal and professional development of the personality, innovative learning makes active search for new personal-oriented conceptions and technologies of higher pedagogical education, aimed at teacher's training as a subject of professional work and development. Key words: self-improvement, professional self-improvement, professional development of the personality, willingness to professional self-improvement, future teacher's training.